Neonatal mortality rate trends and adjusted rates at a tertiary maternity hospital in Qatar: a six-year review - Samawal Lutfi (17136049) (2023)
Introduction Neonatal mortality is a major public health concern, with approximately 2.4 million neonates dying each year in the first 28 days of life worldwide. The Women's Wellness & Research Center (WWRC) is a large tertiary maternity hospital in Qatar that aims to improve the intact survival of its NICU graduates. This quality review examines the trends in neonatal mortality rates in WWRC over the last six years (2015-2020) and compares them to historical data and other NICUs around the world. Methods This is a retrospective quality review study that examines all neonatal deaths in WWRC from 2015 to 2020. To provide a standardized review process, the study used a structured neonatal-specific mortality trigger tool and electronic medical records were used to validate the data. The Neonatal Mortality Rate (NMR), Early Neonatal Mortality Rate (ENMR), and Late Neonatal Mortality Rate (LNMR) are calculated, as well as an adjusted NMR (aNMR) for infants born at or below 23 weeks gestation. The study includes all infants who died in WWRC, regardless of where they died, and examines infants who died in the NICU after the neonatal period as a percentage of all NICU admissions during the chosen period. Results During the study period, there were 101,172 live births more than 20 weeks of gestational age. A total of 586 died in the first 28 days of life yielding a crude NMR of 5.8 deaths per 1000 live births for the study period. Out of these 586 neonatal deaths, 180 infants were born below the threshold of viability (less than 23 weeks) and further, 174 infants died due to conditions incompatible with life. This results in an adjusted neonatal mortality rate (aNMR) of 2.3/1000 live births over the six-year study period. Throughout the 6-year study period, there was a reduction of 23% & 50% in the crude NMR & aNMR, respectively (equivalent to approximately 32.4 fewer deaths in 2020). Similarly, during this time frame, the Infant mortality rate (IMR) dropped by 55%, and the adjusted IMR reduced by 62%. Conclusion This study shows that WWRC has significantly improved over the past six years in lowering the aNMR, with results that are comparable to other NICUs globally. In order to continue making progress in reducing neonatal mortality rates, this study emphasizes the significance of monitoring neonatal mortality rates as a primary quality indicator for NICUs. It also emphasizes the need for continual quality improvement efforts.